Legal Strategies for Corruption Asset Recovery and Public Trust - Wardani, Dian Eka Kusuma; Anggraeni, Mulia; Rizal, Andi (Universitas Brawijaya, 2025)
Recovery of corruption assets is a crucial legal and policy issue, yet Indonesia's history of asset recovery has not yielded significant results due to structural and procedural setbacks. Previous studies by Septiana & Afifah (2022) on civil confiscation and Santosa et al. (2023) on comparative asset forfeiture regulations have examined some aspects of this issue, but lack a comprehensive approach that integrates the principles of the United Nations Convention Against Corruption (UNCAC), domestic law, and the practical challenges faced by third parties. This study examines the procedures established under the UNCAC and their integration into the Indonesian legal framework, with the aim of facilitating the recovery of seized assets in corruption cases. It also investigates the difficulties in verifying asset ownership, the legal framework, and procedures for asset forfeiture. The paper's methodology combines a conceptual approach, which serves as a breakthrough in addressing emerging challenges, with normative research methods. According to the study's findings, the UNCAC addresses asset recovery from corruption crimes in two ways: direct property recovery and recovery through international collaboration. Meanwhile, the confiscation of assets from corruption crimes through prosecution is intended to return assets gained from corruption crimes under Law No. 20 of 2001, which has amended Law No. 31 of 1999, based on confiscation of assets from corruption crimes through civil lawsuits and confiscation of assets from corruption crimes that are difficult to prove through the shifting burden of proof. This research offers a comprehensive strategy that can serve as the foundation for developing a more effective asset recovery policy in Indonesia.